2019
DOI: 10.3389/fimmu.2019.00681
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Tn Immunization Attenuates Hyperoxia-Induced Lung Injury in Neonatal Rats Through Suppression of Oxidative Stress and Inflammation

Abstract: Hyperoxia therapy is often required to treat newborns with respiratory disorders. Prolonged hyperoxia exposure increases oxidative stress and arrests alveolar development in newborn rats. Tn antigen is N-acetylgalactosamine residue that is one of the most remarkable tumor-associated carbohydrate antigens. Tn immunization increases the serum anti-Tn antibody titers and attenuates hyperoxia-induced lung injury in adult mice. We hypothesized that maternal Tn immunizations would attenuate hyperoxia-induced lung in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…We revealed that maternal immunization with Tn vaccine increased neonatal rat serum levels of anti-Tn antibody; reduced mean linear intercept (MLI), lung cytokine stress, and oxidative stress; and increased vascular density and growth factor expressions to normoxic levels in hyperoxia-injured neonatal rats (Chen et al, 2019). These findings suggest that anti-Tn antibody has therapeutic effects on rats with hyperoxia-induced lung injury.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…We revealed that maternal immunization with Tn vaccine increased neonatal rat serum levels of anti-Tn antibody; reduced mean linear intercept (MLI), lung cytokine stress, and oxidative stress; and increased vascular density and growth factor expressions to normoxic levels in hyperoxia-injured neonatal rats (Chen et al, 2019). These findings suggest that anti-Tn antibody has therapeutic effects on rats with hyperoxia-induced lung injury.…”
Section: Introductionmentioning
confidence: 82%
“…In this study, we evaluated the protective effects of anti-Tn monoclonal antibody on alveolar and vascular development in newborn mice exposed to hyperoxia. We demonstrated that hyperoxia increased oxidative stress and inflammation and led to impaired alveolarization and angiogenesis in neonatal rat lungs (Chen et al, 2019). Consequently, we chose a comparable model and demonstrated hyperoxia affected mice angiogenesis in a similar way.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Prolonged exposure of neonatal rats to hyperoxia was reported to result in decreased alveolarization and vascularization similar to those in human bronchopulmonary dysplasia. 2,3 The pathogenesis of BPD is multifactorial, and oxygen toxicity is considered to play a crucial role in the lung injury process that leads to BPD development. 4,5 Currently, no effective therapy is clinically available for treating established lung injury induced by hyperoxia.…”
Section: Introductionmentioning
confidence: 99%